2010
DOI: 10.1017/s0022112010000820
|View full text |Cite
|
Sign up to set email alerts
|

Aspect ratio dependence of heat transfer and large-scale flow in turbulent convection

Abstract: The heat transport and corresponding changes in the large-scale circulation (LSC) in turbulent Rayleigh-Bénard convection are studied by means of three-dimensional direct numerical simulations as a function of the aspect ratio Γ of a closed cylindrical cell and the Rayleigh number Ra. The Prandtl number is P r = 0.7 throughout the study. The aspect ratio Γ is varied between 0.5 and 12 for a Rayleigh number range between 10 7 and 10 9 . The Nusselt number N u is the dimensionless measure of the global turbulent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
162
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 166 publications
(175 citation statements)
references
References 50 publications
13
162
0
Order By: Relevance
“…When convection sets in, plumes of the same type (cold or hot) have the tendency to cluster giving rise to a large-scale flow [84]. It has been found in experiments [85] and DNS [27] that the morphology of the large-scale circulation depends on the form of the cell and the aspect ratio, particularly at intermediate Rayleigh numbers. For example in a cell with aspect ratio of one essentially one LSC roll is expected.…”
Section: Nu-ra Scalingmentioning
confidence: 99%
See 4 more Smart Citations
“…When convection sets in, plumes of the same type (cold or hot) have the tendency to cluster giving rise to a large-scale flow [84]. It has been found in experiments [85] and DNS [27] that the morphology of the large-scale circulation depends on the form of the cell and the aspect ratio, particularly at intermediate Rayleigh numbers. For example in a cell with aspect ratio of one essentially one LSC roll is expected.…”
Section: Nu-ra Scalingmentioning
confidence: 99%
“…In an extension of the theory [32] a full functional dependence for the relations Nu(Ra, P r) and Re(Ra, P r) was suggested that incorporates the varying ratio of both BL thicknesses with respect to each other when the Prandtl number is changed, i.e., with (11) and (27) …”
Section: Scaling Theory By Grossmann and Lohsementioning
confidence: 99%
See 3 more Smart Citations